Effects of a recommended training program, using elastic cords, for enhancing muscle strength on developing the performance level of fall-on-foot skill for free style wrestlers - Hosny Al-Shorbagy, N.; Hafez Mahmoud, A. (World Journal of Sport Sciences, 2010)
Wrestling has evolved from a violence-dependant sport into a sport governed by rule and regulations. Developing physical and technical performances affects results greatly. This research aimed at designing a training program using elastic cords to develop special muscle strength of falling on foots skill for free style wrestler and identifying the effect of the training program on developing the effectiveness of performing falling on foots skill for free style wrestler. Sample was purposefully chosen from Gifted Club - Nasr City free style wrestling team (12 wrestlers) with means age of 15 years. Sample was divided randomly into two groups (6 wrestlers each) to form the experimental and control group. The researchers used the quasiexperimental approach with two groups (experimental and control) and pre / post- tests. The researchers concluded that the post- measurements of the physical variables and technical variables of performing the fall-on-foot skill were significantly enhanced compared to the pre-tests for the control group due to the traditional training program. The post- measurements of the physical variables and technical variables of performing the fall-on-foot skill were significantly enhanced compared to the pre-tests for the experimental group due to the recommended training program. The experimental group showed significant enhancements on the postmeasurements of the physical variables and technical variables of performing the fall-on-foot skill compared to the control group.